Earth Bible sermons - Punnackadu, Mathew Koshy, 1956-; George, Dee; I.S.P.C.K. (Organization); Church of South India (Delhi ISPCK, 2016)
Contributed articles.
Includes bibliographical references.
Keywords: Bible. -- Criticism, interpretation, etc; Human ecology -- Religious aspects -- Christianity; Human ecology in the Bible; Ecotheology; Environmental ethics -- Religious aspects -- Christianity; Free will and determinism -- Biblical teaching